Mosquito control actions affect chironomid diversity in temporary wetlands of the Upper Rhine Valley. Issue 18 (18th September 2019) - Theissinger, Kathrin; Röder, Nina; Allgeier, Stefanie; Beermann, Arne J.; Brühl, Carsten A.; Friedrich, Anna; Michiels, Susanne; Schwenk, Klaus
Abstract: The Upper Rhine Valley, a "hotspot of biodiversity" in Germany, has been treated with the biocide Bacillus thuringiensis var. israelensis (Bti) for mosquito control for decades. Previous studies discovered Bti nontarget effects in terms of severe chironomid abundance reductions. In this study, we investigated the impact of Bti on species level and addressed the community composition of the nontarget family Chironomidae by use of community metabarcoding. Chironomid emergence data were collected in three mosquito‐control relevant wetland types in the Upper Rhine Valley. For all three sites the chironomid species composition, based on operational taxonomic units (OTUs), was different to varying degrees in the Bti‐treated samples versus control samples, ranging from a significant 63% OTU reduction to an OTU replacement. We assumed that predatory chironomids are less prone to Bti than filter feeders, as the latter feed on floating particles leading to direct ingestion of Bti. However, a comparable percentage of predators and filter feeders (63% and 65%, respectively) was reduced in the Bti samples, suggesting that the feeding strategy is not the main driver for Bti sensitivity in chironomids. Finally, our data was compared to a three‐year‐old data set, indicating possible chironomid community recovery due to species recolonization a few years after the last Bti application. Considering the currently discussed worldwide insect decline we recommend a rethinking of the usage of the biocide Bti, and to prevent its ongoing application especially in nature protection reserves to enhance ecological resilience and to prevent boosting the current biodiversity loss.